An Ethnobotanical study of medicinal plants in Taşköprü (Kastamonu–Turkey) - Senkardes, Ismail; Dogan, Ahmet; Emre, Gizem (Frontiers in Pharmacology, 2022)
This pharmaceutical ethnobotanical research was carried out in Taşköprü District in Kastamonu, in northern Anatolia. It assembles the elaborations of plants used as folk medicines, and the ethnopharmacological data collected in the course of in-person semi-structured interviews with an open-ended questionnaire. The study’s aims were two-fold: gathering and identifying plants that the local inhabitants use therapeutically, and recording information related to traditional folk medicine (primarily for humans, and if extant for animals). The plants were gathered during several outings between May 2016 and July 2018. The organization of the data was based on the use-reports (UR) and was done according to the ICPC-2 classification. In addition, cultural importance index (CI) and informant consensus factor (FIC) calculations were made for the data collected. The research identified 101 plant taxa of 31 families used in folk medicine. Of these, 89 were wild and 12 were cultivated taxa. In total, 499 medicinal uses were determined. The CI values indicated that the most significant medicinal plant specimens were Pinus nigra subsp. pallasiana (0.78), P. sylvestris var. hamata (0.75) and Plantago lanceolata, P. major subsp. intermedia and P. major subsp. major (0.58 each). The most prevalent families were Asteraceae (2.14), Rosaceae (1.93), Pinaceae (1.81) and Plantaginaceae (1.74). Respiratory system (0.95), skin and subcutaneous tissue (0.94), nervous system (0.92) and circulatory system disorders (0.88) and ethnoveterinary uses (0.89) had the highest FIC values. The most frequently used preparation process was observed to be decoction (38.4%) and the most commonly utilized plant parts were aerial (21%). Along with recording 20 plant taxa as medicinal plants for the first time, this study documented a total of 303 new therapeutic uses. This study concludes with the finding that traditional knowledge of medicinal plants remains prevalent in Taşköprü, particularly among its rural inhabitants.